The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s0100-41582005000500001
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and rice disease management

Abstract: ABSRACTThe element silicon (Si) is not considered an essential nutrient for plant function. Nevertheless, Si is absorbed from soil in large amounts that are several fold higher than those of other essential macronutrients in certain plant species. Its beneficial effects have been reported in various situations, especially under biotic and abiotic stress conditions. The most significant effect of Si on plants, besides improving their fitness in nature and increasing agricultural productivity, is the restriction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 30 publications
(52 reference statements)
2
36
0
1
Order By: Relevance
“…The results of this study showed that application of silica gel and sodium silicate effectively reduced the severity and incidence of rice leaf blast. These results further confirm previous reports (Cai et al, 2008;Datnoff et al, 1997;Rodrigues and Datnoff, 2005). The results also revealed that plants treated with silica gel suffered lower levels of disease severity as compared with those treated with sodium silicate.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that application of silica gel and sodium silicate effectively reduced the severity and incidence of rice leaf blast. These results further confirm previous reports (Cai et al, 2008;Datnoff et al, 1997;Rodrigues and Datnoff, 2005). The results also revealed that plants treated with silica gel suffered lower levels of disease severity as compared with those treated with sodium silicate.…”
Section: Discussionsupporting
confidence: 92%
“…This indicates that Si application reduces the expansion of lesion as score 4 and 5 only appeared on Si-treatment. This might be as a result of physical barrier created by Si in the cuticle layer to reduce lesion, through organo silicon compound that accumulated in the wall of epidermal cell (Volk et al, 1958;Rodrigues et al, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…Silicium forms insoluble (phytoliths) and soluble aggregates (orthosilicic acid polymers), intertwined with cellulose and cell wall components, making them strong and flexible, thus protecting plant tissue against water, air and microorganisms action (Rodrigues and Datnoff, 2005). Vegetable physiologists consider silicium as an essential element for plants, however, has been reported that the presence of silicium benefit crops, by induction of resistance and protection against various biotic and abiotic factors attributed in part to the accumulation and polymerization in the cell walls, which constitutes a mechanical barrier against attack by pathogens and insects (Epstein, 1999).…”
Section: Discussionmentioning
confidence: 99%